Nghiên cứu lí thuyết cơ chế phản ứng giữa C2H và H2S. - Huệ, Nguyễn Thị Minh; Trị, Trần Quốc; Tân, Trần Văn (Vietnam Journal of Chemistry, 2012)
The reaction mechanism of the Ethynyl radical and H2S have been studied by the Density Functional Theory (DFT) using the B3LYP functional and the 6-311++g(d,p), 6-311++g(3df,2p) basis sets. The potential energy surface (PES) for the C2H+H2S system was also established. Calculated results indicate that products of this reaction can be HC(C)SH + H, H2CC + SH, HCCSH + H, C2H2 + HS. However, the formation of HCCSH + H and C2H2 + HS is the most favorable.